Research on the Performance and Enlightenment of New York Storm Surge Adaptive Landscape Infrastructure - Lu Feng (E3S Web of Conferences, 2019)
In the context of global warming, the study of the resilient city and resilient landscape has received more and more attention. In this work, New York is used as an example to explore the practical applications of storm surge adaptive landscape infrastructure. The vulnerability of New York in storm surges and New York’s plans for resilient city construction are introduced. Then according to the spatial distribution, through field research, questionnaires and data integration, the landscape infrastructure cases of beaches, waterfront parks, inland parks, nature areas and streets are studied, and their performance in Sandy is analysed. After that, under the guidance of resilient city theories and storm surge adaptation strategies, the experience that can be learned from these cases is summarized.